2001
DOI: 10.1086/320912
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Dusty Warm Absorber in MCG −6-30-15 with the [ITAL]Chandra[/ITAL] High-Energy Transmission Grating

Abstract: We present detailed evidence for a warm absorber in the Seyfert 1 galaxy MCG-6-30-15 and dispute earlier claims for relativistic O line emission. The HETG spectra show numerous narrow, unresolved (FWHM ∼ < 200 km s −1 ) absorption lines from a wide range of ionization states of N, O, Mg, Ne, Si, S, Ar, and Fe. The O VII edge and 1s 2 − 1snp resonance line series to n = 9 are clearly detected at rest in the AGN frame. We attribute previous reports of an apparently highly redshifted O VII edge to the 1s 2 − 1snp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
209
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(233 citation statements)
references
References 34 publications
21
209
2
1
Order By: Relevance
“…This suggests that the dust is similar to Galactic dust and resides within the warm ionized gas, and may significantly affect the observed soft X-ray spectrum (Komossa & Fink 1997 and references therein;Komossa & Bade 1998). Spectroscopic evidence for dust in X-ray warm absorbers has now been found by Lee et al (2001) in the Chandra gratings observation of MCG-6-30-15 (this seems to have been confirmed by the very recent XMM-Newton data of Turner et al 2003). This high resolution spectrum exhibited a sharp drop 2 at ∼0.7 keV consistent with the L3 absorption edge from neutral Fe.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…This suggests that the dust is similar to Galactic dust and resides within the warm ionized gas, and may significantly affect the observed soft X-ray spectrum (Komossa & Fink 1997 and references therein;Komossa & Bade 1998). Spectroscopic evidence for dust in X-ray warm absorbers has now been found by Lee et al (2001) in the Chandra gratings observation of MCG-6-30-15 (this seems to have been confirmed by the very recent XMM-Newton data of Turner et al 2003). This high resolution spectrum exhibited a sharp drop 2 at ∼0.7 keV consistent with the L3 absorption edge from neutral Fe.…”
Section: Introductionsupporting
confidence: 65%
“…Of the three models shown here, the depth of the O  edge is greatest when r = 175 pc, with τ OVII = 0.15. The Fe  edge from the dust is noticeable as a small notch just redward of the O  edge, as was observed by Lee et al (2001). The majority of the opacity below 0.3 keV is due to absorption by He , as was found in the lukewarm absorber of Kraemer et al (2000).…”
Section: The Location Of the Dwasupporting
confidence: 54%
See 2 more Smart Citations
“…ref [8]) often strictly focused on data 2 keV, as the main effect of these warm absorbers are below this energy (e.g. ref [58]), notably the two strong edges of O VII and O VIII at ∼ 0.74 keV and ∼ 0.87 keV, respectively [59] (note that for RX J1131-1231 at z = 0.658, this restricts the bulk effect of any possible WA to energies 0.5 keV). However, subsequent detailed analyses accounting for the multizone warm absorber present in this source still obtained consistent spin measurements [55,52,60] and concluded that the relativistic iron line is robust to the precise details of the WA (e.g.…”
Section: No Evidence For Complex Absorption In Rx J1131-1231mentioning
confidence: 99%